Dummy run study for outlining and plan quality of intensity-modulated radiotherapy in elderly patients with newly diagnosed glioblastoma: The Japan clinical oncology group study JCOG1910 (AgedGlio-PIII) - Tomohiro Ono; Megumi Uto; Yohei Mineharu; Yoshiki Arakawa; Mitsuhiro Nakamura; Teiji Nishio; Hiroshi Igaki; Keiji Nihei; Satoshi Ishikura; Yoshitaka Narita; Takashi Mizowaki; Brain Tumor Study Group and Radiation Therapy Study Group of the Japan Clinical Oncology Group (Radiation Oncology)
Abstract Background A dummy run was conducted to ensure the quality of intensity-modulated radiotherapy (IMRT) before registration in a randomized phase III study of elderly patients with newly diagnosed glioblastoma by the Japan Clinical Oncology Group 1910 (JCOG1910). Methods All 41 institutions enrolled in this study were required to report outlining that included gross tumor volume (GTV), clinical target volume (CTV), planning target volume (PTV), and treatment planning for one benchmark case. First, deviations in outlining were evaluated using the Dice similarity coefficient (DSC) and mean distance agreement (MDA), compared to reference targets delineated by the research secretariat. Second, the participating institutions were required to create treatment plans for arms A (40.05 Gy in 15 fractions) and B (25 Gy in 5 fractions) using IMRT techniques. The quality of the outlining and dose-volume criteria for each target and organs at risk were evaluated. Results Six institutions failed to adhere to the protocol and required revision due to insufficient GTV outlining, not considering anatomical barriers for CTV, and modifying PTV against protocols. Compared to the reference outlining, the means and standard deviations of DSC and MDA were 0.37 ± 0.19 and 9.41 ± 3.99 mm for GTV; 0.80 ± 0.08 and 4.31 ± 1.85 mm for CTV; and 0.83 ± 0.05 and 4.23 ± 1.45 mm for PTV, respectively. Regarding dose-volume criteria, 40 of the 41 institutions met the per-protocol limits; only one was within the acceptable limits. Conclusions Several institutions demonstrated deviations in outlining that necessitated revisions. Thus, appropriate feedback and periodic sharing of information with participating institutions is necessary in the upcoming prospective JCOG1910 study.